Measuring time use in development settings - Seymour, Greg; Malapit, Hazel J.; Quisumbing, Agnes R. (World Bank, 2017)
This paper discusses the challenges associated with collecting time-use data in developing countries. The paper suggests potential solutions, concentrating on the two most common time-use methods used in development settings: stylized questions and time diaries. The paper identifies a significant lack of rigorous empirical research comparing these methods in development settings, and begins to fill this gap by analyzing data from Women’s Empowerment in Agriculture Index surveys in Bangladesh and Uganda. The surveys include stylized questions and time diary estimates for the same individual. The study finds limited evidence that stylized questions are more feasible (in terms of interview length) but also less accurate, compared with time diaries. These results are attributed to the relatively greater cognitive burden imposed on respondents by stylized questions. The paper discusses the importance of broadening the scope of time-use research to capture the quantity and quality of time, to achieve richer insights into gendered time-use patterns and trends. The paper suggests a path forward that combines mainstream time-use data collection methods with promising methodological innovations from other disciplines.